Coeliac disease and autoimmunity. Issue 579 (January 1974) - Lancaster-Smith, M. J.; Swarbrick, E. T.; Perrin, J.; Wright, J. T.
Abstract : Among fifty-seven patients with proven coeliac disease three also had thyrotoxicosis, two insulin dependant diabetes, three fibrosing alveolitis and one each had vitiligo, rheumatoid arthritis and cryptogenic cirrhosis. Autoantibodies were demonstrated in twelve of thirty-one patients tested, seven of these twelve had one of the above associated conditions. Antireticulin antibodies were found in seven of twenty-three patients tested, and there was a significant association with dietary gluten. These findings appear to support that coeliac disease is associated with disturbed immunity and that a predisposition to autoimmunity may exist.